2017
DOI: 10.1007/s00210-017-1386-z
|View full text |Cite
|
Sign up to set email alerts
|

Probable mechanisms involved in the antipsychotic-like activity of methyl jasmonate in mice

Abstract: Psychosis is a chronic neuropsychiatric disorder that affects millions of individuals worldwide and impairs the quality of life and productivity of the patients. The clinical efficacy of antipsychotic drugs has been compromised by adverse effects, relapse, and therapeutic failures, thus necessitating search for alternative agents. Methyl jasmonate (MJ) is a bioactive compound reported to have beneficial effects in various neurological disorders. This study was undertaken to investigate the antipsychotic-like e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Thirty minutes thereafter, each animal from groups 2-7 received intraperitoneal injection of apomorphine (APO) (2 mg/kg) and mice were placed immediately in a transparent observation chamber (20 cm × 20 cm × 23 cm), and ste-reotype behaviors were observed for 2 min at 5, 10, 20, 30, 40, 50 and 60 min after APO injection according to the stereotype behavioral scale: 0 = absence of stereotype behavior; 1 = presence of stereotype movements of the head; 2 = intermittent sniffing; 3 = chewing; 4 = intense licking. Thereafter, Kruskal-Wallis test was used for the statistical analysis, which was performed separately to the time points at 5, 10, 20, 30, 40, 50 and 60 min, as previously described [30]. After each mouse session, the observation chamber was cleaned with 70 % ethanol to remove residual odour from previous mouse.…”
Section: Effect Of Morin On Apomorphine-induced Stereotypymentioning
confidence: 99%
“…Thirty minutes thereafter, each animal from groups 2-7 received intraperitoneal injection of apomorphine (APO) (2 mg/kg) and mice were placed immediately in a transparent observation chamber (20 cm × 20 cm × 23 cm), and ste-reotype behaviors were observed for 2 min at 5, 10, 20, 30, 40, 50 and 60 min after APO injection according to the stereotype behavioral scale: 0 = absence of stereotype behavior; 1 = presence of stereotype movements of the head; 2 = intermittent sniffing; 3 = chewing; 4 = intense licking. Thereafter, Kruskal-Wallis test was used for the statistical analysis, which was performed separately to the time points at 5, 10, 20, 30, 40, 50 and 60 min, as previously described [30]. After each mouse session, the observation chamber was cleaned with 70 % ethanol to remove residual odour from previous mouse.…”
Section: Effect Of Morin On Apomorphine-induced Stereotypymentioning
confidence: 99%
“…[ 16 ], which have shown that MJ exhibited sedative effect and enhanced GABAergic neurotransmission. These findings have led to extensive studies on the effects of MJ on neurological disorders and the mechanisms underlying its neuroprotective activity in rodents [ 17 - 23 ]. This review presents the documented evidence on the neuroprotective activities of MJ and the mechanisms underlying its therapeutic potentials in neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although MJ is widely used to treat depression, nervousness, and improve memory in aromatherapy, the finding that MJ demonstrated sedative effect and enhanced GABA currents [Hossain et al, ] provided the first experimental evidences supporting a mechanistic basis for its therapeutic benefits in neuropsychiatric disorders. Moreover, MJ demonstrated adaptogenic, antiamnesic, and antipsychotic activities in rodents [Eduviere et al, ; Umukoro et al, ; Annafi et al, ] and exhibited antidepressant‐like activity in mice subjected to acute stress models of forced swimming (FST) and tail suspension (TST) tests. It also attenuated depressive‐like symptoms induced by lipopolysaccharide in mice [Umukoro et al, ; Adebesin et al, ].…”
Section: Introductionmentioning
confidence: 99%